2015
DOI: 10.1021/acs.jpcb.5b07346
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of a Piperidinium-Based Room-Temperature Ionic Liquid Exhibiting Scanning Rate Dependence

Abstract: The structural flexibility and conformational variety of the ions in room-temperature ionic liquids (RTILs) have significant effects on their physicochemical properties. To begin a systematic study of the thermodynamic properties of nonaromatic RTILs, 1-methyl-1-butylpiperidinium bis(fluorosulfonyl)amide ([Pip1,4][FSA]) was selected as the first sample. In addition to the rotational flexibility of the alkyl group, the [Pip1,4](+) cation has characteristic ring-flipping flexibility, which is very different from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 50 publications
3
43
0
Order By: Relevance
“…In Figure 2b, two peaks of PP 14 + can be observed at 283 and 714 cm −1. [ 20 ] In general, the peak intensity of the cations was too weak to discern the change in the Raman spectrum and various mole ratios in this study, but the intensity of the AlCl 4 − anions remained stable, as expected. Vibrational assignments of anionic and cationic species in those IL electrolytes are shown in Table S1, Supporting Information.…”
Section: Resultssupporting
confidence: 68%
“…In Figure 2b, two peaks of PP 14 + can be observed at 283 and 714 cm −1. [ 20 ] In general, the peak intensity of the cations was too weak to discern the change in the Raman spectrum and various mole ratios in this study, but the intensity of the AlCl 4 − anions remained stable, as expected. Vibrational assignments of anionic and cationic species in those IL electrolytes are shown in Table S1, Supporting Information.…”
Section: Resultssupporting
confidence: 68%
“…Such melting behavior is particularly common in materials which exhibit polymorphism, and it has been recently reported that ionic liquid exhibits polymorphic behavior. [32][33][34][35][36][37][38][39] Also in this work, there are several solid phases which have different segmental motion due to polymorphism, such solid phase exhibited melting behavior below the temperature corresponding to the solidus line. Additionally, we got composition dependence of heat of fusion as Fig.…”
Section: Ionic Conductivity and Viscosity Measurementsmentioning
confidence: 68%
“…The differential scanning calorimetry (DSC) curves of the organic salts 1 – 4 are shown in Figure 2. Only 4 showed different phase transition behavior, i.e., very small exothermic peaks for the crystallization at ~279 K and the crystalline phase transition at ~299 K. Because it is not uncommon for ILs to show similar behavior, these phase changes could be governed by the very slow dynamics in 4 [27,28]. In addition to this behavior, a clear endothermic peak for the melting process at 363 K appeared in the DSC curve during the heating process.…”
Section: Resultsmentioning
confidence: 99%